STRATEGI MARKETING PUBLIC RELATIONS SCARLETT WHITENING DALAM MEMBANGUN CITRA MELALUI ENDORSEMENT - Sarah Sonya (Program Studi Ilmu Komunikasi Universitas Mataram, 2023)
Marketing Public Relations Scarlett Whitening uses endorsement methods on social media to promote its products through influencers and public figures. Influencers must review the entire range of products starting from body care, hair care, and skin care. Apart from that, you have to be able to promote the series as attractively as possible so that the influencer's followers are even more interested in trying and buying it. Reviewing Scarlett Whitening products must match what the influencer said so that there is no conflict with the influencer's followers just because the influencer's review did not match the expectations when the public reviewed it. With current endorsement services, the company's production is increasing because of the interesting talent from an influencer's review. Keywords: Endorsement, Marketing Public Relations, Review